Index-based placement and distributed generation sizing based on heuristic search - N. Z., Mohd Ali; I., Musirin; Z., Khalidin; Mohd Redzuan, Ahmad (IEEE, 2011)
Transmission loss, voltage regulation and voltage drop are three main issues in distribution system. In recent years, distributed generations (DG) installation approaches have been addressed widely in many parts of the world. Depending on their operating characteristics and location, DG can significantly affect the power losses and voltage profile in distribution system. Thus, prior to the installation of DG into a system, offline study is a priori so that under-compensation and over-compensation can be avoided. This paper presents a method for DG placement based on a voltage stability index, while its sizing is optimally identified using an optimization technique in order to minimize power losses in the distribution system. The proposed technique was tested on an IEEE 10 radial distribution system. As for the DG sizing, an optimization technique based on approximate method (AM) is used and indicated promising results.